Saturday

August 23, 2014

August 23, 2014

Posted by **Matt** on Tuesday, March 16, 2010 at 3:22pm.

- Math -
**Reiny**, Tuesday, March 16, 2010 at 4:30pmRS

= 1/cos2x + sin2x/cos2x

= 1/(cos^2x - sin^2x) + 2sinxcosx/cos^2x - sin^2x)

= (1 + 2sinxcosx)/[(cosx+sinx)(cosx-sinx)]

= (sin^2x + 2sinxcosx + cos^2x)/[(cosx+sinx)(cosx-sinx)]

= (sinx + cosx)^2/[(cosx+sinx)(cosx-sinx)]

= (sinx + cosx)/(cosx - sinx)

= LS

- Math -
**Matt**, Tuesday, March 16, 2010 at 11:08pmThank you very much!

**Related Questions**

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...

precalculus - For each of the following determine whether or not it is an ...

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

MATH - Hi, I really need help with these questions. I did some of them halfway, ...

algebra - Can someone please help me do this problem? That would be great! ...

Math(Please check) - Use the fundamental identities to simplify the expression. ...

trig 26 - simplify to a constant or trig func. 1. sec ²u-tan ²u/cos ²v+sin ²v ...